Handbook of aging and the social sciences - Binstock, Robert H.; George, Linda K.; Cutler, Stephen J.; Hendricks, Jon; Schulz, James H. (Handbooks of aging., 2006)
A comprehensive summary and evaluation of recent research on the social aspects of aging. Aging is examined from the perspectives of many disciplines and professions including anthropology, bioethics, demography, economics, epidemiology, law, political science, psychology, and sociology.